An Analysis of The Effects of Special Allocation Funds, Labor Force Participation Rate, Average Years of Schooling, and Life Expectancy on Poverty Alleviation in Ngawi Regency for the 2003-2024 Period - Kikisani, Tika Feby; Suryo Bintoro , Nugroho (Journal of Development Economic and Social Studies, 2025)
This study aims to analyze the effect of the Special Allocation Fund (DAK), Labor Force Participation Rate (LFPR), Average Years of Schooling (AYS), and Life Expectancy (LE) on the poverty rate in Ngawi Regency during the period 2003–2024. Poverty in Ngawi Regency is a complex issue that requires serious attention from both local and central governments, especially in the context of fiscal allocation. This research uses a quantitative approach with the Vector Error Correction Model (VECM) method to analyze the long-term and short-term relationships between the independent variables and the poverty rate. In general, an increase in DAK allocation, labor force participation, education level, and public health status contributes to reducing poverty. This study is expected to serve as input for formulating more strategic regional fiscal policies focused on sustainable poverty alleviation efforts.